Local Wisdom Literacy: Promising Context Integration in Algebra Learning - Meryani Lakapu; Wilfridus Beda Nuba Dosinaeng; Kristoforus Djawa Djong; Samuel Igo Leton; Nelly Fitriani (RANGE: Jurnal Pendidikan Matematika, 2026)
Indonesian students’ mathematical literacy skills, particularly in algebra, are still relatively low, as shown by the results of PISA 2022. A significant contributing factor is the limited relevance of teaching materials to students’ real-life contexts. This study introduces an innovative approach by developing algebra teaching materials based on local wisdom—referred to as local wisdom literacy—as a meaningful context for improving mathematical literacy among seventh-grade junior high school students. The novelty of this study lies in the integration of traditional Timorese cultural practices, such as weaving patterns, local measurement systems, and indigenous numerical reasoning, into formal algebra instruction. Using the ADDIE development model, this Research and Development (R&D) study produced culturally embedded materials that were validated by experts, with validity scores of 85.4% for content and 85% for assessment instruments. The materials were also considered highly practical (96.93% by students, 96% by teachers) and effective, as indicated by a moderate average N-Gain of 0.42 in student learning outcomes. In addition to improving conceptual understanding and mathematical literacy, the developed materials serve as a culturally responsive pedagogical model that is in line with the objectives of the Merdeka Curriculum and supports the preservation of local culture. This study provides a contextual and humanistic alternative in algebra learning, which offers pedagogical value and cultural significance